Respons Ketahanan Sumberdaya Genetik Lokal Cabai (Capsicum frutescens L. dan Capsicum annuum L.) terhadap Infeksi Virus Daun Keriting Kuning - Andarwening, Freestina; Sobir; Deden Derajat Matra, (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2022)
Pepper Yellow Leaf Curl Virus is a major disease in chili peppers, causing severe damage and yield loss. The use of resistant genotypes is an effective way of controlling the disease. Developing resistance genotypes requires a series of plant breeding processes, starting with the identification of new potential genetic sources. The study aimed to identify the resilience response of 10 cayenne pepper genotypes (C. frustecsens L.) and 4 chili pepper genotypes (C. annuum L.) collection of the Center for Tropical Horticultural Studies (PKHT) to acquire resistant plant candidates. Planting and inoculation were carried out in a greenhouse at Tajur experimental station, and detection of PYLCV was carried out in the molecular laboratory by DNA amplification method using degenerate primers Begomovirus SPG1 and SPG2. The results showed that all plants were infected by PYLCV and it was also confirmed by PCR detection. Based on the disease severity, the CB-EL genotype was categorized as resistant plants with a severity value of 8.89% and the longest incubation period, 21-50 days. Genotypes CB-BA and CB-BJ (13.13%), CB-CA and PKHT-1 (15.56%), CR-SA and PKHT-7 (17.78%) and PKHT-6 (20.00%) were categorized as moderately resistant. Disease severity and disease incidence had a broad-sense heritability values of 0.47 and 0.61, and were categorized as moderate and high heritability, respectively.Keywords: disease severity, Bemisia tabaci, genotype, heritability, selection